A STUDY OF MECHANICAL VENTILATION ON CARDIOVASCULAR OUTPUT (Journal of Pharmaceutical Negative Results, 2023)
Background: This study is measuring the impact of mechanical ventilation on cardiovascular output. Mechanical ventilation improves the gaseous exchange. According to, it also helps to modify the blood flow system. Purpose of the study: A group of 30 patients was included in this study. Those patients are continuously assigned to either a control group or a mechanical ventilation group. The control group consists of conventional protective mechanical ventilation. serving 24 hours it is concluded that the control group received no c but the mechanical group received continuous mechanical ventilation. Before and after 24 hours cardiovascular output was measured.Problem statement: It is observed that mechanical ventilation increased cardiac output significantly among the patient in the mechanical ventilation group in contrast to the control group. It is concluded that the paints that are suffered from cardiac disorders mechanical ventilation became a fruitful treatment for them. Method materials: The data sources will include conference processing pre-reviewed journal articles and other relevant sources. Qualitative data analysis method has been used in this research. The output of this systematic review will be used to create a conclusion about the mechanical ventilation effect on cardiovascular output.Major findings: The study is a discussion about the importance of closely monitoring patients who received mechanical ventilation ensuring to receive the required oxygen and ventilation. This study became a review of the available literature.Novelty: This study became a review of the available literature. The strategy of searching will include mechanical ventilation-related keywords.